2014
DOI: 10.1016/j.sbspro.2014.09.125
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Employees’ Perceptions of Competency Models on Employability Outcomes and Organizational Citizenship Behavior and the Moderating Role of Social Exchange in this Effect

Abstract: Competencies of human resource, which are considered as factors creating innovation and value to organizations, are becoming extremely important for organizations. An understanding of competency-based development will improve employees' performance and therefore will help to improve the performance of the organization. Our research was conducted in Istanbul by using convenient sampling method on 175 participants working in banking, telecommunications, health care, aeronautical and food industries. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
0
6
0
3
Order By: Relevance
“…Menggunakan teori ini untuk berpendapat bahwa, ketika seseorang merasa puas dalam organisasi, maka mereka akan membalasnya dan meningkatkan kinerja. Serim et al, (2014) mengemukakan bahwa hubungan di tempat kerja memiliki unsur-unsur dari teori pertukaran sosial. Teori pertukaran sosial mendominasi ciri kepribadian dan sikap seseorang.…”
Section: Pendahuluanunclassified
“…Menggunakan teori ini untuk berpendapat bahwa, ketika seseorang merasa puas dalam organisasi, maka mereka akan membalasnya dan meningkatkan kinerja. Serim et al, (2014) mengemukakan bahwa hubungan di tempat kerja memiliki unsur-unsur dari teori pertukaran sosial. Teori pertukaran sosial mendominasi ciri kepribadian dan sikap seseorang.…”
Section: Pendahuluanunclassified
“…The significant influence of personal competence on OCB is also in line with the findings of Kurniawan (2014) stating that competence and commitment have a significant effect on OCB. Human resource competencies, which are considered as factors that create innovation and value for organizations, are very important for organizations (Serima et al, 2014). While the results of research from Suhardi and Syaifullah (2017) have different findings, that competence does not significantly influence organizational citizenship behavior.…”
Section: Resultsmentioning
confidence: 99%
“…'The primary role of competency models is to align employee behaviour to firm strategy, it is suggested that their effectiveness should be evaluated through the lens of organisational culture or climate theories, both of which suggest that a strategy's success depends on how employees throughout an organisation understand and act on that strategy, because the purpose of a competency model is to influence strategically aligned behaviour by outlining the behavioural themes that are expected and rewarded across all jobs in the organization ' (Sanchez & Levine, 2009 as cited in Serim, Demirba g, & Yozgat, 2014, p. 1102. Employee outcomes are influenced by the perception of competency models by employees in the organisation.…”
Section: Competency and Competency Modelmentioning
confidence: 99%